The Effectiveness of TikTok Features in Teaching Writing of Procedure Text - Berlianty, Tasha; Suhartono, Luwandi; Rosnija, Eni (Journal of English Language and Education, 2025)
Writing is an essential language skill, yet many students struggle to write coherent procedure texts. Although previous studies explored TikTok in teaching writing, few examined its effectiveness for procedure texts. This study aimed to determine whether TikTok features are effective in teaching tenth-grade students at SMAN 11 Pontianak to write procedure texts during the 2024/2025 academic year. Using a pre-experimental one-group pre-test and post-test design, 33 students were taught using TikTok’s video-sharing and direct-messaging features. The paired sample t-test result (t = 4.19 1.69389, p 0.05) and an effect size of 0.729 (moderate) showed significant difference in students’ writing performance. These findings confirm that TikTok features are effective for students’ ability to write procedure texts.